Guesswork Television. - Guesswork Television (Collingwood, VIC : Guesswork Television, 2012)
"Guesswork Television works with the finest and funniest creators and stars in Australian television and pairs them with teams that are passionate about making great, global TV. Guesswork Television is a full- service production company with offices in Melbourne and Sydney, specialising in narrative comedy, authored documentary and studio entertainment shows."
Title from title screen (viewed on 27 July 2018)
Mode of access: Available Online. Address as at 30/07/2018
Selected for archiving
Keywords: Television -- Production and direction -- Australia; Australian